Occupational Characteristics and Management Measures of Sporadic COVID-19 Outbreaks From June 2020 to January 2021 in China: The Importance of Tracking Down “Patient Zero” - Feng, Maohui; Ling, Qiong; Xiong, Jun; Manyande, Anne; Xu, Weiguo; Xiang, Boqi (Frontiers in Public Health, 2021)
There are occupational disparities in the risk of contracting COVID-19. Occupational characteristics and work addresses play key roles in tracking down “patient zero.” The present descriptive analysis for occupational characteristics and management measures of sporadic COVID-19 outbreaks from June to December 2020 in China offers important new information to the international community at this stage of the pandemic. These data suggest that Chinese measures including tracking down “patient zero,” launching mass COVID-19 testing in the SARS-CoV-2-positive areas, designating a new high- or medium-risk area, locking down the corresponding community or neighborhood in response to new COVID-19 cases, and basing individual methods of protection on science are effective in reducing the transmission of the highly contagious SARS-CoV-2 across China.